2019
DOI: 10.1080/22221751.2019.1660590
|View full text |Cite
|
Sign up to set email alerts
|

H3N2 avian influenza viruses detected in live poultry markets in China bind to human-type receptors and transmit in guinea pigs and ferrets

Abstract: The H3N2 influenza viruses became widespread in humans during the 1968 H3N2 pandemic and have been a major cause of influenza epidemics ever since. Different lineages of H3N2 influenza viruses are also commonly found in animals. If a different lineage of H3N2 virus jumps to humans, a human influenza pandemic could occur with devastating consequences. Here, we studied the genetics, receptor-binding properties, and replication and transmission in mammals of 15 H3N2 avian influenza viruses detected in live poultr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 30 publications
1
31
0
Order By: Relevance
“…and their nasal turbinates, soft palate, tonsils, trachea, lung, spleen, kidneys, and brain were collected for virus titration. For the respiratory droplet transmission studies, groups of three ferrets were inoculated i. n. with 10 6 PFU of test virus and housed in specially designed cages inside an isolator as described previously [6,7,46]. Twenty-four hours later, three naïve ferrets were placed in an adjacent cage (4 cm away), separated by a double-layered net divider.…”
Section: Ferret Studymentioning
confidence: 99%
“…and their nasal turbinates, soft palate, tonsils, trachea, lung, spleen, kidneys, and brain were collected for virus titration. For the respiratory droplet transmission studies, groups of three ferrets were inoculated i. n. with 10 6 PFU of test virus and housed in specially designed cages inside an isolator as described previously [6,7,46]. Twenty-four hours later, three naïve ferrets were placed in an adjacent cage (4 cm away), separated by a double-layered net divider.…”
Section: Ferret Studymentioning
confidence: 99%
“…Live poultry markets have played pivotal roles in the genesis of novel AIVs (Zhang et al 2013a;Han et al 2014;Deng et al 2015;Cui et al 2016;Liang et al 2016;Guan et al 2019). There are large numbers of live poultry markets in China.…”
Section: Emergence and Genetic Evolutionmentioning
confidence: 99%
“…Data from genome analysis of the past three IAV pandemics, except for the first identified 1918 H1N1 pandemic that remains a mystery, demonstrated that a pandemic emerged from viral reassortment with a human virus gene segment(s) and a nonhuman HA gene segment producing a major viral antigen [ 19 ]. Extensive studies on receptor binding specificities of IAVs from different hosts [ 19 , 256 ] have indicated that a nonhuman HA gene must acquire mutations to recognize α2,6Neu5Ac for efficient human-to-human transmission, leading to the development of several techniques for monitoring and assessing IAV pandemic potential, including a viral NA-based assay [ 257 ], a glycan microarray assay [ 258 ], an evanescent-field-activated fluorescence scanner type glycan array [ 259 ] and a glycan strip test [ 260 ]. However, occasional direct pig-to-human [ 261 ] and human-to-pig [ 262 ] transmission of swine and human IAVs, respectively, both of which preferentially bind to α2,6 sialyl glycans, and some avian IAVs, including HPAI H5N1 [ 263 ], H7N9 [ 264 ], H9N2 [ 265 ], H7N2 and H7N3 [ 266 ], that were reported to have increased binding to human-type α2,6Neu5Ac have not yet caused a pandemic.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%